Pengembangan Sistem Surveilans dalam Pencegahan dan Pengendalian Infeksi pada RSU Haji Surabaya - Anugrah Rasisputra; Achmad Arwan; Faizatul Amalia (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
RSU Haji Surabaya is a public hospital in Surabaya that caters to all levels of society on a social, economic and religious level. On the basis of Regulation of the Minister of Health No. 27 of 2017 Article 3 paragraph 5 states that the infection prevention and control (PPI) process must be carried out with surveillance activities. Surveilance is the process of continuous recording and analysis to obtain data that is specific to infection data in this study. Some of the infections that are recorded and analyzed are Phlebitis, CVC, VAP, UTI, and SSI. Manual survailance by RSU Haji Surabaya still involves some human error. A surveilance system is therefore required to minimize errors. This system will help user enter data and analyze trends. A web-based monitoring system will be developed to make it easier for users to use the system when using a desktop or mobile phone. This study will use an object-oriented approach and apply the MVC design developed on the waterfall method and use the calculation formula for the PPI indicator to calculate the infection pattern. In the need analysis requirement there are 48 functional needs and 6 actors. Functional tests in the form of units, integration and validation produce 100% valid results, and non-functional tests in the form of compatibility produce results that the system can execute on different browsers and platforms.